2020
DOI: 10.11002/kjfp.2020.27.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of Rehmannia glutinosa dried at different drying temperature

Abstract: Rehmannia glutinosa (RG) is a widely cultivated medicinal crop in Korea. Its rhizomes are commonly distributed in dried form as a food or traditional medicine. However, very little research into the drying methods for R. glutinosa has been conducted. This study was performed to determine the effect of the drying temperature on the quality characteristics of R. glutinosa. The famous domestic cultivar 'Dagang' was used for the study. The drying experiments were carried out at 40, 50, 60, 70, and 80℃ in a hot air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…2c). Previous analysis have revealed that during long-term storage, samples with a moisture content of less than 12% show minimal quality changes, including changes in appearance and texture [24]. However, traditional practice to dry R. glutinosa samples is not really suitable to maintain its quality as they applied sun drying that can easily get contaminated, thereby reducing quality [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c). Previous analysis have revealed that during long-term storage, samples with a moisture content of less than 12% show minimal quality changes, including changes in appearance and texture [24]. However, traditional practice to dry R. glutinosa samples is not really suitable to maintain its quality as they applied sun drying that can easily get contaminated, thereby reducing quality [25].…”
Section: Resultsmentioning
confidence: 99%
“…FT-NIR was performed following previously described methods [16]. Absorbance spectra for ground R. glutinosa in a glass vial (5 mm internal diameter) were collected using the TANGO FT-NIR spectrometer (Billerica, MA, USA) with the InGaAs detector, a broadband light source (50 W), interferometer, and a quartz halogen lamp.…”
Section: Fourier Transform Near-infrared Spectroscopy (Ft-nir) Analysismentioning
confidence: 99%